Temporal trends of care practices, morbidity, and mortality of extremely preterm infants over 10-years in South Wales, UK - Lieve Boel (Nature Portfolio, 2020)
Abstract Contemporary outcome data of preterm infants are essential to commission, evaluate and improve healthcare resources and outcomes while also assisting professionals and families in counselling and decision making. We analysed trends in clinical practice, morbidity, and mortality of extremely preterm infants over 10 years in South Wales, UK. This population-based study included live born infants < 28 weeks of gestation in tertiary neonatal units between 01/01/2007 and 31/12/2016. Patient characteristics, clinical practices, mortality, and morbidity were studied until death or discharge home. Temporal trends were examined by adjusted multivariable logistic regression models and expressed as adjusted odds ratios (aOR) with 95% confidence intervals (95% CI). A sensitivity analysis was conducted after excluding infants born at < 24 weeks of gestation. In this population, overall mortality for infants after live birth was 28.2% (267/948). The odds of mortality (aOR 0.93, 95% CI [0.88, 0.99]) and admission to the neonatal unit (0.93 [0.87, 0.98]) significantly decreased over time. Non-invasive ventilation support during stabilisation at birth increased significantly (1.26 [1.15, 1.38]) with corresponding decrease in mechanical ventilation at birth (0.89 [0.81, 0.97]) and following admission (0.80 [0.68–0.96]). Medical treatment for patent ductus arteriosus significantly decreased over the study period (0.90 [0.85, 0.96]). The incidence of major neonatal morbidities remained stable, except for a reduction in late-onset sepsis (0.94 [0.89, 0.99]). Gestation and centre of birth were significant independent factors for several outcomes. The results from our sensitivity analysis were compatible with our main results with the notable exception of death after admission to NICU (0.95 [0.89, 1.01]). There were significant improvements in survival and reduction of late-onset sepsis of extreme preterm infants in South Wales between 2007 and 2016. The sensitivity analysis suggests that some of the temporal changes observed were driven by improved outcomes in the most preterm of infants. Clinical practices related to respiratory support have changed but significant variations in clinical practices and outcomes between centres remain unexplained. The adoption of regional evidence-based clinical guidelines is likely to improve outcomes and reduce variation.